PROSES PENJADWALAN JANGKA PENDEK DENGAN THEORY CONSTRAINT ASAS PRIORITAS BAHAN DAN ALAT YANG DIPRODUKSI DALAM KEGIATAN OPERASI KAMAR BEDAH DI RUMAH SAKIT UMUM PEKERJA - Eka Riadi; Adelina Suryati (Gapenas Publisher, 2023)
This study aims to determine the short-term scheduling process with the theory constraint (TOC) of priority of materials and tools produced in surgical room operations activities in general hospital workers, the research method used in the study is a descriptive type with quantitative primary data collection and secondary data. Data collection techniques using observing, recording, and documenting. Request goods with a hospital information system (HER) account. The study was conducted at the General Workers Hospital in June 2023 The results of the records documented include BHP (Consumables), medical devices and electricity usage